Role of Medicinal Plants in Treatment of Inflammatory Diseases (Kindle, 2022)
Medicinal plants are known as healthy sources for the prevention of different inflammatory and oxidative stress-related diseases. Currently there have been increasing interests in the benefit of medicinal plants. They possess a lot of phytochemical constituents with anti-inflammatory and antioxidant functions including phenolic compounds and carotenoids which have anti-inflammatory and antioxidant characteristics such as chain breaking antioxidants. Intake of carotenoids has revealed a significant decrease in the risk of several chronic and degenerative disorders. Phenolic compounds are commonly found in medicinal plants and food products and mainly consisted of phenolic acids, flavonoids and tannins. These compounds have a wide range of anti-inflammatory and antioxidant characteristics. Therefore, in this book, we aimed to review anti-inflammatory and antioxidant activities of medicinal plants for treatment of inflammatory diseases.
Keywords: Medicinal Plants; Treatment; Inflammatory Diseases